Occupational Risk Factors of Carpal Tunnel Syndrome on Workers: A Literature Review - Amin, Fauziah; Oginawati, Katharina (Riviera Publishing, 2023)
The median nerve at the wrist becomes crushed in a condition known as carpal tunnel syndrome (CTS), which causes pain, numbness, and tingling in the worker's hand's palm. Risk elements for CTS include things like uncomfortable body posture at work, repetitive hand motions, and vibration exposure. Reviewing prior research on the connection between CTS and potential risk factors such worker hand posture, exposure to hand-arm vibrations, and repetitive hand movements is the goal of this study. The research approach involves searching for relevant articles using the terms carpal tunnel syndrome AND (occupational risk factors OR uncomfortable posture OR hand-arm vibrations OR repeated hand movements) in databases like ScienceDirect, PubMed, ResearchGate, and Scopus. The study indicates that Carpal Tunnel Syndrome is related to repetitive hand movements, hand-arm vibrations, and awkward hand posture during work. This research implies the importance of awareness about occupational safety. Additionally, the study suggests that job designs considering repetitive hand movements, vibrations, and incorrect posture can reduce the risk of Carpal Tunnel Syndrome. Therefore, it is hoped that organizations and workers can collaborate to create a safer, healthier, and more productive work environment.